Pemasaran Video Dokumenter Sebagai Strategi Pengembangan Ekonomi Sumber Daya Alam Di Desa Mambal - Oktarini, Luh Nik; Aryani, Putu Diah; Dewi, Ni Made Yunita; Priandita, Made Wahyu; Purwaka, I Made Gede; Astari, Ni Komang Alit Tri; Rahayu, Ni Komang Sukma Apti; Dewi, Ni Kadek Swasti; Narayana, I Made Duta Pria; Januarta, I Wayan Eka Saputra (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2025)
Documentary video marketing is an effective strategy for developing natural resource potential in Mambal Village. The village has rich natural resources, including a jogging track that can attract tourists. This study aims to explore the role of documentary video marketing in promoting and developing natural resource-based economy in the village. The research used a qualitative approach with data collection through interviews, observations, and documentation. The findings show that marketing through documentary videos can raise awareness about the existing natural potential, attract tourists, and have a positive impact on the local economy. In conclusion, documentary video marketing can be an effective tool for sustainable natural resource-based economic development in Mambal Village